Immunogenicity and effectiveness of COVID-19 booster vaccination among people living with HIV: a systematic review and meta-analysis - Cheng, Meng-Qun; Li, Rong; Weng, Zhi-Ying; Song, Gao (Frontiers in Medicine, 2023)
The effect of booster vaccinations with the Coronavirus Virus Disease (COVID-19) vaccine in people living with hiv (PLWH) remains unknown. In this study, we aimed to investigate the immunogenicity and effectiveness of booster vaccination with the COVID-19 vaccine in PLWH.Literature research was done through PubMed, Embase, Cochrane Review, and Web of Science up to July 4, 2023. Pooled estimates were calculated and compared using the DerSimonian and Laird method for a random effects model. Randomized controls trials and observational studies were both considered for inclusion.We included 35 eligible studies covering 30,154 PLWH. The pooled immune response rate (IRR) of PLWH after the COVID-19 booster vaccination was 97.25% (95% confidence interval [CI], 93.81-99.49), and similar to healthy control (HC) (Risk Ratio [RR] = 0.98, 95% CI, 0.96-1.00). The pooled IRR for PLWH with CD4 + T cell counts ≤ 200 was 86.27 (95% CI, 65.35-99.07). For Omicron variants, the pooled IRR for PLWH after booster dose was 74.07% (95% CI, 58.83-89.30), and the risk of IRR was reduced by 10% in PLWH compared with HC (RR = 0.90, 95% CI, 0.80-1.00). The T-cell immune response of PLWH was found to be comparable to HC (p ≥ 0.05). Subgroup analyses revealed that mRNA vaccines produced relatively high IRR in PLWH compared to other vaccines. In addition, the results showed that booster vaccination appeared to further reduce the risk of COVID-19 related infections, hospitalizations, and deaths compared with primary vaccination.It was shown that booster vaccination with the COVID-19 vaccine provided high IRR in PLWH and still produced a desirable moderate IRR in PLWH with CD4 + T-cell count ≤ 200. Importantly, the humoral and T-cell responses to booster vaccination in PLWH were comparable to HC, and similar results were observed with the SARS-CoV-2 Omicron variant. Our review strongly emphasizes the effect of mRNA vaccine booster vaccination in PLWH in eliciting desirable protective IRR. Furthermore, booster vaccination appears to further reduce the risk of COVID-19 infection, hospitalization, and death in PLWH compared to primary vaccination. However, more evidence is needed to confirm its effectiveness.